Age model, elemental geochemistry and magnetic data of cores MD03-2673, MD03-2679 and MD03-2685 - Nathan Stevenard; Catherine Kissel; Aline Govin; Camille Wandres (PANGAEA, 2024)
These datasets contain the tie-points used to construct the chronologies and the continuous and high resolution elemental and magnetic data of three couples of cores: MD03-2673-74Cq, MD03-2679-80Cq and MD03-2685-84Cq. These cores were retrieved South of Iceland, on Gardar and Björn drifts (56 to 61°N). These data are used to investigate the past changes in intensity of the Iceland Scotland Overflow Water (ISOW) over the last 400 ka (1ka = 1000 years) and include basaltic-derived concentrations proxies and grain-size proxies, both recording the past ISOW intensity. The chronologies were align to the ice-core age scale AICC2012 (Bazin et al., 2013; Veres et al., 2013), but for convenience, we also propose a revised AICC2023 chronology (Bouchet et al., 2023).